Dynamics of Adaptive Immune Cell and NK Cell Subsets in Patients With Ankylosing Spondylitis After IL-17A Inhibition by Secukinumab - Jiang, Yutong; Yang, Mingcan; Zhang, Yanli; Huang, Yefei; Wu, Jialing; Xie, Ya; Wei, Qiujing; Liao, Zetao; Gu, Jieruo (Frontiers in Pharmacology, 2021)
Background Anti-IL-17A therapy is successfully used in patients with Ankylosing Spondylitis (AS) to achieve and maintain remission. However, the influence on the composition of the immune system is not apparent. Our prospective study was to explore the changes in immune imbalance regarding T cell, B cell and nature killer (NK) cell subsets after secukinumab treatment in AS patients. Methods Immune cell distribution of 43 AS patients treated with secukinumab for 12 weeks and 47 healthy controls (HC) were evaluated. Flow cytometry using monoclonal antibodies against 23 surface markers was applied to explore the frequencies of lineage subsets. The differences between HC, AS pre-treatment, and post-treatment were compared using the paired Wilcoxon test, Mann-Whitney U test, and ANOVA. Results AS patients had altered immune cell distribution regarding T cell and B cell subsets. Apart from activated differentiation of CD4+ T cell, CD8+ T cell and B cell, a higher level of cytotoxic T (Tc) 2 cells and Tc17 cells was noted in AS patients. We confirmed that helper T (Th) 1 cells became decreased; however, Th17 cells and T follicular helper (Tfh) 17 cells went increased in AS. After 12 weeks of secukinumab therapy, CRP and ASDAS became significantly decreased, and meanwhile, Th1 cells, Tfh17 cells and classic switched B cells were changed towards those of HC. A decreased CRP was positively correlated with the decrease in the frequency of naïve CD8+ T cells (p=0.039) and B cells (p=0.007) after secukinumab treatment. An elevated level of T cells at baseline was detected in patients who had a good response to secukinumab (p=0.005). Conclusions Our prospective study confirmed that AS patients had significant multiple immune cell dysregulation. Anti-IL-17A therapy (Secukinumab) could reverse partial immune cell imbalance.